2016
DOI: 10.1016/j.rmed.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect costs of COPD and its comorbidities: Results from the German COSYCONET study

Abstract: COPD is associated with substantially higher costs than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
68
4
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 27 publications
13
68
4
17
Order By: Relevance
“…Similar results were demonstrated for absenteeism in our study: approximately between 520 and 3700€/patient. The trend observed in our study about a positive correlation between the amount of indirect costs and severity of COPD is in agreement with that reported by Wacker et al [28] ranging from 8621 to 27,658€ according to severity [26,28]. A study performed from the perspective of the employers in Canada presents a significant percent of indirect costs (51%) and shows that the higher the severity, the higher the indirect costs per patient: $1079 (mild), $1554 (moderate) and $2198 (severe and very severe) [29], which was supported by our observations.…”
Section: Resultssupporting
confidence: 94%
“…Similar results were demonstrated for absenteeism in our study: approximately between 520 and 3700€/patient. The trend observed in our study about a positive correlation between the amount of indirect costs and severity of COPD is in agreement with that reported by Wacker et al [28] ranging from 8621 to 27,658€ according to severity [26,28]. A study performed from the perspective of the employers in Canada presents a significant percent of indirect costs (51%) and shows that the higher the severity, the higher the indirect costs per patient: $1079 (mild), $1554 (moderate) and $2198 (severe and very severe) [29], which was supported by our observations.…”
Section: Resultssupporting
confidence: 94%
“…In agreement with this study, a considerable number of studies have reported that COPD is a significant societal economic burden, associated with increased HCRU and higher health care costs, among COPD population versus control population. [18][19][20][21][22][23][24][25][26][27] As in our observations, previous studies have reported that key drivers for higher direct costs of COPD include inpatient hospitalizations 12,17,22,24,26,28 and increased medication use. 12,17,18,24 Further contributory factors to higher direct costs in COPD patients are comorbidities 17,19,23,27 and hospital admissions resulting from comorbidities.…”
Section: Discussionsupporting
confidence: 57%
“…We found that 33% of patients were supported by family caregivers at home, as were 50% of those with advanced airflow limitation. The indirect costs increase as airflow limitation deteriorates [5]; we found that the in-home care rate increased as airflow limitation progressed. Of all caregivers, 13.6% quit their jobs to stay home.…”
Section: Discussionmentioning
confidence: 63%